2017
DOI: 10.1111/jocn.13798
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a nurse‐supervised home exercise programme on improving patients’ perceptions of the benefits and barriers to exercise: A randomised controlled trial

Abstract: Physical exercise in a clinical arena should not be considered the exclusive domain of physical therapists; the team could collaborate with nurses to play a core role in making physical exercise for patients an essential practice of care in a multidisciplinary team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…Gait speed increased between baseline and 20 weeks above the MDC 90 calculated for this population (0.26 m/s), so that 11 out of 17 participants from both groups increased gait speed above this value. A previous study found an increase in normal gait speed of 0.12 m/s after a home‐based program with high adherence rates . Another study that implemented a combined exercise program in CKD patients stages 3‐4 also found an increase of 0.28 m/s in gait speed after a 12‐week intervention .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Gait speed increased between baseline and 20 weeks above the MDC 90 calculated for this population (0.26 m/s), so that 11 out of 17 participants from both groups increased gait speed above this value. A previous study found an increase in normal gait speed of 0.12 m/s after a home‐based program with high adherence rates . Another study that implemented a combined exercise program in CKD patients stages 3‐4 also found an increase of 0.28 m/s in gait speed after a 12‐week intervention .…”
Section: Discussionmentioning
confidence: 90%
“…A previous study found an increase in normal gait speed of 0.12 m/s after a home-based program with high adherence rates. 26 Another study that implemented a combined exercise program in CKD patients stages 3-4 also found an increase of 0.28 m/s in gait speed after a 12-week intervention. 27 In our study, we found no differences between groups.…”
Section: Discussionmentioning
confidence: 97%
“…Awareness of recommendations and adherence are closely related [65]. It should be emphasized that the importance of awareness of recommendations can only be developed as a result of patient education, an essential element of dialysis care [6,66,67,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Primary health care professionals including GPs, physiotherapists, pharmacists and nutritionists will be incorporated into the recruitment strategy. Evidence suggests that advice from these groups promotes engagement in physical activity programmes [2427]. An official MFL launch, addressed by the president of the university and a government minister, will take place 2 weeks prior to trial commencement and will receive local and national media coverage.…”
Section: Methodsmentioning
confidence: 99%